(untitled) (Boletin Médico de Postgrado, 2020)
A quasi-experimental study of time series was carried out to evaluate the effectiveness of propranolol in the treatment of cutaneous vascular malformations in 48 patients attending the Dermatology Service of the Hospital Central Universitario Dr. Antonio Maria Pineda during the period February - July 2018. The results show that there are statistically significant differences (p <0.05; p<0,0001) before and after treatment with propranolol starting one month post-treatment which are kept until six months, related to size, color, consistency and temperature of lesions. We hope that these results will encourage the use of propranolol as a non-invasive therapeutic option in the treatment of cutaneous vascular malformations.